The Influence of Management Capabilities to the Effectiveness of School Implementation - Ahmad, Syarwani (International Journal of Economics, Business and Management Studies, 2012)
This research aims to know the influence of the leadership and head master's management capabilities on school implementation. Study is quantitative in nature. Differential analysis is used to test the hypotheses. Normality test is also employed using Liliefors, and Barlett technique. The findings suggested that there is a direct effect on headmaster's leadership to the principal's school management capability. Direct effect on headmaster's leadership to the effectiveness of school implementation is also highlighted in this research. Moreover, direct effect of management capability on the effectiveness of school has also been identified. This research strongly supported the contention that effectiveness of school implementation is dominantly influenced by headmasters and their management capability.